2020
DOI: 10.6118/jmm.20030
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor Symptoms: More Than Temporary Menopausal Symptoms

Abstract: Vasomotor symptoms (VMS), such as hot flashes and night sweating, are classic menopausal symptoms experienced by a majority of perimenopausal and postmenopausal women. VMS have received a great deal of attention due to their relationship with cardiometabolic risk. Further, accumulating evidence indicates that VMS are associated with an increased risk of several chronic diseases, including metabolic syndrome, type 2 diabetes mellitus, nonalcoholic fatty liver diseases, and osteoporosis in perimenopausal and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…23 In addition to a similar population in which they occur, these conditions seem to be influenced by the same factors, such as growth hormone, vitamin D, and physical exercise. 23 However, several studies have reported that VMS were associated with the risk of osteoporosis in menopausal women, 10 in contrast to the negative relationship between VMS and sarcopenia observed in this study. Such discrepancies imply that complex physiologic mechanisms are involved in the relationships between VMS, and muscle and bone health, which should be determined by a further study.…”
Section: Menopausal Vasomotor Symptoms and Sarcopeniacontrasting
confidence: 88%
See 1 more Smart Citation
“…23 In addition to a similar population in which they occur, these conditions seem to be influenced by the same factors, such as growth hormone, vitamin D, and physical exercise. 23 However, several studies have reported that VMS were associated with the risk of osteoporosis in menopausal women, 10 in contrast to the negative relationship between VMS and sarcopenia observed in this study. Such discrepancies imply that complex physiologic mechanisms are involved in the relationships between VMS, and muscle and bone health, which should be determined by a further study.…”
Section: Menopausal Vasomotor Symptoms and Sarcopeniacontrasting
confidence: 88%
“…9 VMS are associated with several chronic disorders, including obesity, insulin resistance, metabolic syndrome, osteoporosis, and cardiovascular diseases. 10 Several epidemiologic studies have reported an association between VMS and obesity assessed using body mass index (BMI) and waist circumference. 11 However, such anthropometric measures are limited because they do not reflect the exact body composition, such as the percentage of adipose tissue versus muscle tissue.…”
mentioning
confidence: 99%
“…Hot flashes are characterized by sudden strong fever or sweating on the face, neck and upper chest area, as well as palpitations, anxiety, irritability, and panic. In addition, the peripheral and central body temperatures change (Freedman et al, 1995;Freedman, 2000;Ryu et al, 2020). Hot flashes often occur at night, interfering with sleep, affecting mental health, and lowering quality of life (de Zambotti et al, 2014;Stuenkel, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that up to 85% of women experience hot flashes. Hot flashes are associated with an increased risk of chronic diseases such as 10.3389/fnagi.2022.993955 obesity, metabolic syndrome, insulin resistance, non-alcoholic fatty liver, cardiovascular disease, and osteoporosis (Lee et al, 2012;Kwon et al, 2016;Ryu et al, 2016Ryu et al, , 2018, and they are regarded as an early warning sign of cardiovascular disease (Rathnayake et al, 2019;Ryu et al, 2020). However, the pathophysiology of hot flashes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that vasomotor symptoms are biomarkers of impaired cardiometabolic conditions, not just temporary symptoms of menopausal women. 30 Furthermore, the timing of the onset of high blood pressure is usually at the beginning of menopause. Symptoms of female hypertension (such as hot flashes and palpitations) are often mistaken for menopause.…”
Section: Raise Awareness Of Menopausal Transition and Improve Health ...mentioning
confidence: 99%